Performance optimization for the viscoelastic surfactant using nanoparticles for fracturing fluids. Issue 10 (2nd October 2020) - Mpelwa, Musa; Zheng, Yahui; Tang, Shanfa; Pu, Mingzheng; Jin, Lijun
Abstract: In order to optimize the viscoelastic properties and temperature-resistance for the sodium 2, 2'-(propane-1, 3-diylbis(stearoylazanediyl))diethanesulfonate Gemini viscoelastic surfactant, the effects caused by the addition of nanoparticles were investigated. The viscous and rheological behaviors and microstructures of surfactant solutions with/without magnesium oxide (MgO) or lipophilic silicon dioxide (SiO2 ) nanoparticles were studied using rheometer and field emission scanning microscopy electron microscopy (FESEM). The experimental results showed that the addition of optimal nanoparticle mass fractions significantly increases the viscoelastic properties for the viscoelastic micelle solutions at 90 °C. The enhancements in viscoelastic properties are ascribed to the formation of network structures due to the addition of nanoparticles. The use of nanoparticles showed promising improvements to be applied for fracturing fluids at high temperatures.